2021
DOI: 10.3390/ma15010040
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Investigation of WC-Based Coatings Prepared by HVOF onto AZ31 Substrate

Abstract: In this paper, three commercial cermet powders, WC-Co-Cr, WC-Co and WC-Cr3C2-Ni, were sprayed by the High Velocity Oxy Fuel (HVOF) method onto magnesium alloy AZ31 substrate. The coatings were investigated in terms of their microstructure, phase analysis and residual stress. The manufactured coatings were analyzed extensively using optical microscopy (OM), X-ray diffraction (XRD), scanning (SEM) and transmission electron microscopy (TEM). Based on microstructure studies, it was noted that the coatings show sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…WC–Co‐based coatings protected the steel substrates from wet and dry abrasion conditions and also observed that finer WC particles were associated with increased wear resistance 6–11 . Jonda et al 12 . and Mendez‐Medrano et al 13 .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…WC–Co‐based coatings protected the steel substrates from wet and dry abrasion conditions and also observed that finer WC particles were associated with increased wear resistance 6–11 . Jonda et al 12 . and Mendez‐Medrano et al 13 .…”
Section: Introductionmentioning
confidence: 96%
“…WC-Co-based coatings protected the steel substrates from wet and dry abrasion conditions and also observed that finer WC particles were associated with increased wear resistance. [6][7][8][9][10][11] Jonda et al 12 and Mendez-Medrano et al 13 evaluated the microstructure and phase characterization of tungsten carbide and chromium carbide coatings. They noticed that the X-ray diffractometry (XRD) pattern of the coatings indicated the WC and Cr 3 C 2 decarburization phases and disintegration of WC particles occurs, resulting in substantial amounts of W 2 C, W, and Co 3 W 3 C. Schwetzke et al 14 and Matikainen et al 15 investigated the microstructure of WC-based coatings on mild steel substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, corrosion resistance, abrasive wear and cavitation erosion were tested [26,27]. Moreover, the detailed microstructure investigations were carried out [28]. Testing the resistance of coatings to erosive wear caused by solid particles is the next stage of the research plan.…”
Section: Introductionmentioning
confidence: 99%
“…Also thermal spraying methods could be used in order to manufacture coatings on magnesium alloys, as follow: cold spray [29], arc spray [30,31], detonationgun [32], flame spray [33] and plasma spray [34,35]. As it was described in previous papers [36,37], high velocity oxy fuel (HVOF) method is the most promising, especially for cermet coatings deposition. Although coatings sprayed on AZ31 alloy substrates are already well described [38], there is a gap in the literature related to the application of coatings on AZ91 alloy substrates.…”
Section: Introductionmentioning
confidence: 99%